Performance of weanling pigs fed diets containing various lactose sources - O'Quinn, P.R.; Bergstrom, J.R.; Loughmiller, J.A.; Musser, R.E.; Nessmith, W.B.Jr; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two growth trials were conducted to evaluate the effects of replacing the lactose provided by dried whey in the phase II diet with either deproteinized whey or an alternative lactose source, DairyLac 80®. No differences in performance observed among pigs fed diets containing 10% dried whey or deproteinized whey or DairyLac 80®. These trials indicate that deproteinized whey and DairyLac 80® can be used to replace the lactose contained in dried whey for starter pig diets.
Keywords: Swine; Weanling pigs; Lactose; Deproteinized whey; DairyLac 80®